2006
DOI: 10.1109/tasc.2006.871222
|View full text |Cite
|
Sign up to set email alerts
|

Cold Test Results of the Inner Triplet Orbit Correctors for the LHC

Abstract: The inner triplet orbit correctors for the LHC, MCBX and MCBXA, underwent acceptance tests at superfluid helium temperature at CERN, before shipping to FNAL for integration in the cold masses. A total of 27 MCBX (Horizontal-Vertical Dipole Correctors), of which 9 MCBXA (with nested Sextupole-Dodecapole insert), are needed for the LHC, including spares. The paper discusses the test protocols for series magnets, and reports the results of quench performance and cold magnetic measurements. The peculiarities of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Another similar method, often referred to as the 'degaussing procedure' or the 'demagnetization cycle', was previously developed for LTS accelerator magnets. Repeated current sweep cycles with decreasing overshooting amplitudes around the target current can establish a current distribution with alternating patterns in a filament, which can substantially suppress the field error and temporal drift caused by a combination of flux creep and current redistribution in LTS conducors [52][53][54]. For insulated REBCO coils, however, a similar procedure designed by Yanagisawa et al indicated that the full suppression of the SCF and its relaxation would require an overly large overshoot that is undesirable in practice [16].…”
Section: Excitation Historymentioning
confidence: 99%
“…Another similar method, often referred to as the 'degaussing procedure' or the 'demagnetization cycle', was previously developed for LTS accelerator magnets. Repeated current sweep cycles with decreasing overshooting amplitudes around the target current can establish a current distribution with alternating patterns in a filament, which can substantially suppress the field error and temporal drift caused by a combination of flux creep and current redistribution in LTS conducors [52][53][54]. For insulated REBCO coils, however, a similar procedure designed by Yanagisawa et al indicated that the full suppression of the SCF and its relaxation would require an overly large overshoot that is undesirable in practice [16].…”
Section: Excitation Historymentioning
confidence: 99%